Pengembangan Soal Matematika Berbasis HOTS (Higher Order Thinking Skills) Untuk Siswa SMP - Insani, Sri Ulfa; Utami, Ratna Widianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The aim of this research is to produce Higher Order Thinking Skills of mathematics questions with has good validity, practicality, and effectiveness. Researchers use a research and development design with the ADDIE model. This research is in SMP Negeri 37 Pekanbaru. The research subjects were 36 students in class IX 5 for junior high school students. The techniques data collection used were test with mathematics questions instrument and non-test techniques with validation sheets and practicality sheets instruments. The results showed that the higher Order Thinking Skills of mathematics questions was included in the very valid category with an average score = 4.57. HOTS mathematics questions are also included in the very practical category with an average score = 4.01. Furthermore, the HOTS mathematics questions included the effective category based on the calculation of the value  and , which means that the proportion of students who have achieved KKM is more than 74.99%